2015
DOI: 10.3390/su7067175
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Waste Recycling Behaviour: A Meta-Analytical Review

Abstract: Abstract:In order to increase waste recycling, many studies have been conducted to understand factors that may influence waste recycling behaviour. However, these studies have focused on household contexts rather than other waste generation contexts. As a result, this paper seeks to provide a detailed analysis of previous studies on workplace waste recycling behaviour. Drawing from different databases, 51 relevant studies on workplace waste recycling attitudes and behaviour were meta-analysed. Findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 72 publications
0
48
0
1
Order By: Relevance
“…In her research looking at household decision-making around a wide range of sustainability issues, Scott (2009) showed that students who held strong pro-environmental attitudes and would always recycle whilst at home, failed to do so whilst living in their term-time accommodation. The reason that some of these differences have not come to light is that research tends to focus on a single context and also focus on behaviour within the domestic context (Oke, 2015).…”
Section: C) Inconsistency Between Contextsmentioning
confidence: 99%
“…In her research looking at household decision-making around a wide range of sustainability issues, Scott (2009) showed that students who held strong pro-environmental attitudes and would always recycle whilst at home, failed to do so whilst living in their term-time accommodation. The reason that some of these differences have not come to light is that research tends to focus on a single context and also focus on behaviour within the domestic context (Oke, 2015).…”
Section: C) Inconsistency Between Contextsmentioning
confidence: 99%
“…While factors influencing recycling at home are well established and documented, little is known about factors that may likely promote recycling at work (see [1,20] for a review). Nonetheless, the influence of information on recycling at work has been previously investigated (see [15,[21][22][23] for a review).…”
Section: Information and Recycling Behaviourmentioning
confidence: 99%
“…Workplace waste is now attracting more attention than other waste-generation contexts, such as households [2]. While different factors influencing household waste recycling behaviour have been identified and documented [3], workplaces have been relatively overlooked [4].…”
Section: Introductionmentioning
confidence: 99%